Urban sprawl and agricultural livelihood response in peri-urban Ghana. Issue 2 (3rd May 2020) - Afriyie, Kwadwo; Abass, Kabila; Adjei, Prince Osei-Wusu
ABSTRACT: The paper examines agricultural livelihood effects of urban sprawl and farmers' response in peri-urban Kumasi, Ghana, involving in-depth interviews with sixty farmers (n = 60) and four key informants (n = 4). Greater Kumasi has expanded spatially over time resulting in arable land reduction in the peri-urban interface and affecting households in varying ways. This has evoked different responses from affected farmers including agricultural intensification, extensification, diversification and adoption of off-farm livelihood strategies. While some households made livelihood gains in their response, and some livelihood losses, others neither gained nor lost. A mix of livelihood assets, but more importantly human and social capital, were identified as key determinants of the outcomes of households' livelihood strategies employed. To protect arable land from urban encroachment and reduce peri-urban households' vulnerabilities the following policy interventions are noteworthy: effective spatial planning through institutional strengthening, legislative enforcement and widening market for agricultural goods and expanding non-farm jobs.